Um novo perfil interpolante aplicado ao método de volumes finitos em situações une e bidimensionais - Santório, Carlos Alexandre (2002)
In this report, a new scheme of discretization for the method of finite bulks, called FLEX which was proposed for a simulation of problems ruled by differential equations as type of elliptic and hyperbolic. Its performance was appraised through tests from the literature of numeric methods and through tests developed for all the report. The new scheme showed features of convergence and compatible and comparable stabilities to the traditional schemes of Central Difference, Power Law and Flux-Spline . Its accuracy appeared to depend on the type de physical problem. Physical problems ruled by differential partial elliptic equations implied convectiondiffusion which owns a distribution of the variable flux like one purpose by the FLEX scheme which showed a solution with the level of the error minor, in comparison with the remaining schemes. In the traditional problems case of this class, where there isn t the presence with this specific featuring the results proved to be intermediaries. To hyperbolic problems even with a poor discretization within limits of finite difference to the transient term the new scheme appeared interesting features for a simulation of this kind of phenomena in the same sense to non-refined mails to converge to the solution of reference in the rate greater than the others two schemes which were mentioned here and used in the comparison.